2014
DOI: 10.3389/fpsyt.2014.00013
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Kernels for Coordinate-Based Meta-Analyses of Neuroimaging Studies

Abstract: Peak-based meta-analyses of neuroimaging studies create, for each study, a brain map of effect size or peak likelihood by convolving a kernel with each reported peak. A kernel is a small matrix applied in order that voxels surrounding the peak have a value similar to, but slightly lower than that of the peak. Current kernels are isotropic, i.e., the value of a voxel close to a peak only depends on the Euclidean distance between the voxel and the peak. However, such perfect spheres of effect size or likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
347
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 303 publications
(358 citation statements)
references
References 30 publications
0
347
0
1
Order By: Relevance
“…Where only p or z-values were available, we used the online "Two-sample z/p to t converter" available on the SDM website. All the meta-analyses were performed using the anisotropic effect-size-based algorithms (AES-SDM) (Radua et al, 2012;; Radua et al, 2014). The new version of SDM software allows the use of both the positive features of existing peak-probability methods (such as activation likelihood estimation) and of image-based meta-analyses, using standard effect size and variancebased meta-analytic calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Where only p or z-values were available, we used the online "Two-sample z/p to t converter" available on the SDM website. All the meta-analyses were performed using the anisotropic effect-size-based algorithms (AES-SDM) (Radua et al, 2012;; Radua et al, 2014). The new version of SDM software allows the use of both the positive features of existing peak-probability methods (such as activation likelihood estimation) and of image-based meta-analyses, using standard effect size and variancebased meta-analytic calculations.…”
Section: Methodsmentioning
confidence: 99%
“…To disentangle the contradictory findings reported in the 7 resting-state studies included in their meta-analysis (4 fMRI studies and 3 PET studies), Visintin et al converted the reported peak coordinates to effect-size maps and then voxelwise meta-analyzed the maps using Seed-based d Mapping (SDM) (Radua et al 2012;Radua et al 2014).…”
mentioning
confidence: 99%
“…Differences between the findings of current and previous metaanalyses would provide a clearer picture of the white matter alterations directly related to the illness and those potentially influenced by current antidepressant treatment. We used anisotropic effect size-signed differential mapping (AES-SDM), 45 which is the new version of effect size-signed differential mapping (ES-SDM) 46 and has been successfully applied to dementia with Lewy bodies, 47 childhood maltreatment, 48 bipolar disorder and MDD. 32 Additionally, fibre tracking was performed to demonstrate the most probable tracts passing through the white matter regions of altered FA identified by AES-SDM, providing a more intuitive visual platform to appreciate the meta-analysis results.…”
Section: Introductionmentioning
confidence: 99%